The Long Terminal Repeats of ERV6 Are Activated in Pre-Implantation Embryos of Cynomolgus Monkey - Kui Duan; Chen-Yang Si; Shu-Mei Zhao; Zong-Yong Ai; Bao-Hua Niu; Yu Yin; Li-Feng Xiang; Hao Ding; Yun Zheng (Cells, 2021)
Precise gene regulation is critical during embryo development. Long terminal repeat elements (LTRs) of endogenous retroviruses (ERVs) are dynamically expressed in blastocysts of mammalian embryos. However, the expression pattern of LTRs in monkey blastocyst is still unknown. By single-cell RNA-sequencing (seq) data of cynomolgus monkeys, we found that LTRs of several ERV families, including MacERV6, MacERV3, MacERV2, MacERVK1, and MacERVK2, were highly expressed in pre-implantation embryo cells including epiblast (EPI), trophectoderm (TrB), and primitive endoderm (PrE), but were depleted in post-implantation. We knocked down MacERV6-LTR1a in cynomolgus monkeys with a short hairpin RNA (shRNA) strategy to examine the potential function of MacERV6-LTR1a in the early development of monkey embryos. The silence of MacERV6-LTR1a mainly postpones the differentiation of TrB, EPI, and PrE cells in embryos at day 7 compared to control. Moreover, we confirmed MacERV6-LTR1a could recruit Estrogen Related Receptor Beta (ESRRB), which plays an important role in the maintenance of self-renewal and pluripotency of embryonic and trophoblast stem cells through different signaling pathways including FGF and Wnt signaling pathways. In summary, these results suggest that MacERV6-LTR1a is involved in gene regulation of the pre-implantation embryo of the cynomolgus monkeys.